Bioactivities Screening of Indonesian Marine Bacteria Isolated from Sponges - Nina Artanti; Faiza Maryani; Hani Mulyani; Rizna Triana Dewi; Vienna Saraswati; Tutik Murniasih (ANNALES BOGORIENSES, 2016)
The marine bacteria were cultured in liquid medium under shaking condition were extracted with ethyl acetate. Antidiabetes was measured using inhibition of α-glucosidase inhibitory activity method; antioxidant was measured using DPPH free radical scavenging activity method; antibacterial was tested using disc diffusion method.S creening results showed that at sample concentration of 200 µg/ml, there was significant α-glucosidase inhibitory activity was detected in the extracts of strain sp 7.9 (84% inhibition) and 8.10 (75% inhibition),however the antioxidant activity of these two strains were low only around 30% inhibition, antioxidant activities of other strains were very low.Screening for antibacterial activities using 10µl samples showed that extract of strain Sp 8.5was best for Staphylococcusaureus (14 mm inhibition); Sp 7.9 and Sp 8.5 for Bacillus subtilis (18 mm inhibition); Sp 8.10 for Escherichia coli (10 mm inhibition); Sp 8.9 and Sp 8.10 for Pseudomonas aeuriginosa. Based on these results marine bacteria strain Sp 7.9 and Sp 8.10 were selected to be used for further studies in the isolation of bioactive that has potential as antidiabetes and antibacterial.Results of molecular identification conducted by INACC showed that identity of both strain based on BLAST Homology using NCBI database were Bacillus thuringiensis strain Ou2.